A: [img=94x50]1803dc19ee1df1e.png[/img]
B: [img=179x59]1803dc19fa74975.png[/img]
C: [img=136x52]1803dc1a067981e.png[/img]
D: [img=160x59]1803dc1a11fc728.png[/img]
举一反三
- Suppose population X~N([img=11x18]1803dc19edf699d.png[/img],4), where [img=11x18]1803dc19f88e314.png[/img] is unknown, [img=128x25]1803dc1a0221cf9.png[/img] is the sample from the population, the sample mean is [img=15x22]1803dc1a0acf7b5.png[/img], and the sample variance is [img=16x22]1803dc1a13743b1.png[/img], then the non-statistic of the following is A: 2[img=15x22]1803dc1a1c346e6.png[/img] B: [img=18x46]1803dc1a2464660.png[/img] C: [img=48x48]1803dc1a2d89174.png[/img] D: [img=72x46]1803dc1a36d6cae.png[/img]
- Let's say that population X~N([img=36x26]1803dc1a509e5ed.png[/img]),[img=114x23]1803dc1a594f2d6.png[/img] is the sample of X,[img=15x22]1803dc1a6159fd0.png[/img] is the mean of our sample, and [img=19x22]1803dc1a69f6423.png[/img] is the variance of our sample.Which of the following is not true? A: [img=190x74]1803dc1a75634cd.png[/img] B: [img=118x46]1803dc1a7e668c3.png[/img] C: [img=135x50]1803dc1a8a7f9af.png[/img] D: [img=153x72]1803dc1a9526716.png[/img]
- 1.设随机变量X的密度为[img=186x61]18034ea953ec9dd.png[/img]则常数A=________,概率[img=146x25]18034ea95d30d08.png[/img]__________. A: A=2,P(X>1|X<2)=[img=39x24]18034ea9659b618.png[/img] B: A=-2,P(X>1|X<2)=[img=39x24]18034ea9659b618.png[/img] C: A=2,P(X>1|X<2)=[img=47x44]18034ea9768a8c2.png[/img] D: A=-2,P(X>1|X<2)=[img=47x44]18034ea9768a8c2.png[/img]
- 1.设随机变量X的密度为[img=186x61]17de8981070b17c.png[/img]则常数A=________,概率[img=146x25]17de8981130ab0e.png[/img]__________. 未知类型:{'options': ['A=2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]'], 'type': 102}
- 1.设随机变量X的密度为[img=186x61]17de8981070b17c.png[/img]则常数A=________,概率[img=146x25]17de8981130ab0e.png[/img]__________. 未知类型:{'options': ['A=2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=39x24]17de89811f6f1b0.png[/img]', 'A=2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]', 'A=-2,P(X>;1|X<;2)=[img=47x44]17de89812b3a28c.png[/img]'], 'type': 102}
内容
- 0
设X与Y相互独立,均服从参数为1的指数分布,则P(X+Y<1) A: [img=84x24]18036de4b8088be.png[/img] B: [img=75x24]18036de4bf77b71.png[/img] C: [img=75x24]18036de4c8172a3.png[/img] D: =P(X<1)P(X<1) E: =P(X<0.5)+P(X<0.5) F: >P(X<1)
- 1
设X与Y相互独立,均服从参数为1的指数分布,则P(X+Y<1) A: [img=84x24]1803645ffb36da1.png[/img] B: [img=75x24]180364600306be0.png[/img] C: [img=75x24]180364600c8ab8b.png[/img] D: =P(X<1)P(X<1) E: =P(X<0.5)+P(X<0.5) F: >P(X<1)
- 2
设X与Y相互独立,均服从参数为1的指数分布,则P(X+Y<1) A: [img=84x24]18035b3d47a8410.png[/img] B: [img=75x24]18035b3d50597f9.png[/img] C: [img=75x24]18035b3d59275e6.png[/img] D: =P(X<1)P(X<1) E: =P(X<0.5)+P(X<0.5) F: >P(X<1)
- 3
设X与Y相互独立,均服从参数为1的指数分布,则P(X+Y<1) A: [img=84x24]1803637a2a05d69.png[/img] B: [img=75x24]1803637a32412c9.png[/img] C: [img=75x24]1803637a3ab9225.png[/img] D: =P(X<1)P(X<1) E: =P(X<0.5)+P(X<0.5) F: >P(X<1)
- 4
设X与Y相互独立,均服从参数为1的指数分布,则P(X+Y<1) A: [img=84x24]1802daf0ea2780e.png[/img] B: [img=75x24]1802daf0f1ac337.png[/img] C: [img=75x24]1802daf0f9eeb81.png[/img] D: =P(X<1)P(X<1) E: =P(X<0.5)+P(X<0.5) F: >P(X<1)